Analyzing the Potential Impact of Change Management on Employee Performance in Banking Industry in Kerala - M. Dhanabhakyam; Fahad K.P (PT FORMOSA CENDEKIA GLOBAL, 2024)
The dynamic business landscape necessitates Change Management across industries, notably in the Banking Sector, a significant contributor to India's GDP. This study in Kerala's Banking Industry, featuring major banks like State Bank of India, Canara Bank, Federal Bank, South Indian Bank, ESAF Bank, and Catholic Syrian Bank, employed a convenient sampling method with 100 employees. Findings revealed a significant impact of Change Management on Employee Performance. Recommendations highlight the crucial role of Change Management for organizational competitiveness and employee well-being in the banking sector